Policing methamphetamine problems: a framework for synthesising expert opinion and evaluating alternative policy options. (10th October 2013) - Manning, Matthew; Ransley, Janet; Smith, Christine; Mazerolle, Lorraine; Cook, Alana
Abstract: Increasingly, governments and police agencies require evidence of effectiveness and efficiency with respect to law enforcement policies. The existing "what works" literature, specifically on drug law enforcement, focuses mainly on the effectiveness question when making complex choices between drug policy alternatives, but fails when it comes to incorporating empirical evidence and the experience of key experts in the decision-making process. In addition, little attempt has been made to employ sophisticated techniques to assist in complex policy decision making with respect to funding competing policing policy alternatives. We use the methamphetamine problem in Australia to illustrate a way of evaluating, using multi-criteria analysis, alternative policy options for developing better drug policy.